Edukasi Perilaku Hidup Bersih Dan Sehat Dalam Pencegahan Penyakit Pedikulosis Kapitis Di Pondok Pesantren Al-Huda Desa Sragi Kecamata Songgon Kabupaten Banyuwangi - Elok Aqila Febriani,; Joko Sutrisno,; Prima Dewi Kusumawati,; Reni Nurhidayah, (Journal of Health Science Community, 2022)
Factor from pediculosis capitis in the environment cottage usually caused by a lot teenager students who don't can look after self alone or a number of nature bad that doesn't reflect behavior life clean and healthy . So on study this conducted action gift education behavior life clean and healthy (PHBS) with method counseling . Study this aim for knowing influence gift education to prevention disease pediculosis Capitis at Pondok Islamic Boarding School . Study this held at Pondok Al-Huda Village Islamic Boarding School Sragi Subdistrict Songgon Regency Banyuwangi . Study use type study experiment with design quantitative experiment quasi experimental pre and post design , with sample using simple random sampling as many as 51 respondents . Data analysis using Paired Sample T- Test with condition test normality normally distributed (0.05), however if normality data distribution no fulfilled so will next with Test Wilcoxon.Result from Test Statistics obtained enhancement behavior life clean and healthy 27 respondents (53%) and enhancement behavior prevention disease pediculosis capitis there are 24 respondents (47%). seen that the value of 0.000 which can be interpreted that score not enough from 0.05, so that H1 is accepted means there is influence education behavior life clean and healthy in prevention disease pediculosis Capitis at Pondok Boarding school Giving education behavior live clean and healthy on Students is necessary thing _ conducted in effort prevention disease pediculosis capitis , so that beneficial for subtraction number incident pediculosis Capitis at Pondok Islamic Boarding School.